Helicase-dependent isothermal DNA amplification - Vincent, Myriam (2004)
Polymerase chain reaction is the most widely used method for in vitro DNA amplification. However, it requires thermocycling to separate two DNA strands. In vivo, DNA is replicated by DNA polymerases with various accessory proteins, including a DNA helicase that acts to separate duplex DNA. We have devised a new in vitro isothermal DNA amplification method by mimicking this in vivo mechanism. Helicase-dependent amplification (HDA) utilizes a DNA helicase to generate single-stranded templates for primer hybridization and subsequent primer extension by a DNA polymerase. HDA does not require thermocycling. In addition, it offers several advantages over other isothermal DNA amplification methods by having a simple reaction scheme and being a true isothermal reaction that can be performed at one temperature for the entire process. These properties offer a great potential for the development of simple portable DNA diagnostic devices to be used in the field and at the point-of-care.